Reducing firearm access for youth at risk for suicide in a pediatric emergency department - Chaudhary, Sofia; Doh, Kiesha Fraser; Morris, Emilie; Chivily, Caroline; Washington, Donnetta S.; Gillespie, Scott E.; Jergel, Andrew; Lazarus, Sarah; Costa, Angela; Call, Nathan; Rupp, Jonathan; Simon, Harold K. (Frontiers in Public Health, 2024)
Background: Firearm-related suicide is the second leading cause of pediatric firearm death. Lethal means counseling (LMC) can improve firearm safe-storage practices for families with youth at-risk of suicide. Objectives: To evaluate the feasibility of pediatric emergency department (ED) behavioral mental health (BMH) specialists providing LMC to caregivers of youth presenting with BMH complaints and to test for changes in firearm-safety practices, pre-post ED LMC intervention, as measures of preliminary efficacy. Methods: Prospective pilot feasibility study of caregivers of youth presenting to a pediatric ED with BMH complaints. Caregivers completed an electronic survey regarding demographics and firearm safe-storage knowledge/practices followed by BMH specialist LMC. Firearm owners were offered a free lockbox and/or trigger lock. One-week follow-up surveys gathered self-reported data on firearm-safety practices and intervention acceptability. One-month interviews with randomly sampled firearm owners collected additional firearm-safety data. Primary outcomes were feasibility measures including participant accrual/attrition and LMC intervention acceptability. Secondary outcomes included self-reported firearm-safety practice changes. Feasibility benchmarks were manually tabulated and Likert-scale acceptability responses dichotomized to strongly agree/agree vs. neutral/disagree/strongly disagree. Descriptive statistics were used for univariate and paired data responses. Results: Eighty-one caregivers were approached with 50 (81%) enrolling. Forty-four percent reported having a firearm at home. Eighty percent completed follow-up at 1 week. More than 80% affirmed that ED firearm-safety education was useful and that the ED is an appropriate place for firearm-safety discussions. Fifty-eight percent of participants reported not having prior firearm-safety education/counseling. Among firearm owners (n=22), 18% reported rarely/never previously using a safe-storage device. Fifty-nine percent of firearm owners requested safe-storage devices. At 1-week follow-up (n=40), a greater proportion of caregivers self-reported asking about firearms before their child visited other homes (+28%). Among firearm owners that completed follow-up (n=19), 100% reported storing all firearms locked at 1-week (+23% post-intervention). Ten caregivers reported temporarily/permanently removing firearms from the home. Conclusions: It is feasible to provide LMC in the pediatric ED via BMH specialists to families of high-risk youth. Caregivers were receptive to LMC and reported finding this intervention useful, acceptable, and appropriate. Additionally, LMC and device distribution led to reported changes in safe-storage practices.